Ticks (Acari: Argasidae and Ixodidae) infesting amphibians and reptiles in Northeastern Brazil - De Alcantara, Edna Paulino [UNESP]; Ferreira-Silva, Cristiana [UNESP]; Ávila, Robson Waldemar; De Campos Pacheco, Richard; Martins, Thiago Fernandes; Muñoz-Leal, Sebastián; Honorio Morais, Drausio (Systematic and Applied Acarology Society, 2018)
Ticks collected on 21 different species of amphibians and reptiles captured during 2001 to 2017 in the northeast Brazil were identified. Overall, 227 individuals (185 larvae, 32 nymphs, 7 adults females and 3 males) identified as follow: Amblyomma dissimile, Amblyomma rotundatum, Amblyomma sp. larvae, Ornithodoros mimon, Ornithodoros rietcorreai, and an Ornithodoros sp. Herein, we present 25 new tick-host associations, thus contributing to the knowledge on tick-fauna associated to amphibians and reptiles from Brazilian northeast.
Keywords: Amblyomma; Ectoparasites; Ornithodoros